The Länder in the German energy and climate policy: Distributional issues and federal decision-making - Monstadt, Jochen; Scheiner, Stefan (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
Until today, the academic and political debates on the German energy transition have primarily focused on policy activities and processes at either the national or local level. However, they have largely ignored how the Länder shape the federal decision-making on the allocation of greenhouse gas emissions according to their place-based economic interests. The starting point of this paper is the empirical evidence that effective national climate mitigation policies can go along with considerable and spatially unevenly distributed redistributive effects for regional energy industries, energy consumption sectors and thus public budgets of the Länder. Since the costs and benefits of climate mitigation policies are distributed unevenly, the Länder pursue place-based economic and political interests that shape their climate mitigation programs and their positions in federal decision-making. Based on an analysis of the regional economic interests and of the climate mitigation programs of the Länder, the paper uses the cases of the renewable energy policies and the European emission trading system to demonstrate how (re-)distributional conflicts in climate mitigation policies have been reconciled. The case studies show that redistributive policies could be implemented through concessions to single Länder. They also show that through distributive mechanisms, the externalization of costs to the users played a major role, and that the EU could partially dissolve blockades in decision-making. Contrary to findings in the academic debate on German federalism, federal climate mitigation policies have partially stimulated mechanisms for economic and innovation competition between the Länder. However, the findings also demonstrate that the concessions to regional economic interests have reduced the cost-efficiency and effectiveness of the German energy and climate mitigation policies.